2004
DOI: 10.1002/lsm.20044
|View full text |Cite
|
Sign up to set email alerts
|

60‐minute application of S‐Caine Peel prior to 1,064 nm long‐pulsed Nd:YAG laser treatment of leg veins

Abstract: The S-Caine Peel is safe and effective when applied for 60 minutes prior to laser therapy of leg veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…For such procedures, LT peel is often applied at least 60 minutes before the procedure to ensure adequate pain prevention. Jih and colleagues reported significantly greater pain relief with a 60‐minute application of LT peel versus a placebo peel before 1,064‐nm long‐pulsed Nd:YAG laser treatment of leg veins 15 . The longer‐wavelength lasers have been associated with a greater degree of pain than conventional lasers and may prompt patients to stop therapy due to pain.…”
Section: Efficacy Of the 7% Lidocaine And 7% Tetracaine Peel For Dermsupporting
confidence: 80%
See 1 more Smart Citation
“…For such procedures, LT peel is often applied at least 60 minutes before the procedure to ensure adequate pain prevention. Jih and colleagues reported significantly greater pain relief with a 60‐minute application of LT peel versus a placebo peel before 1,064‐nm long‐pulsed Nd:YAG laser treatment of leg veins 15 . The longer‐wavelength lasers have been associated with a greater degree of pain than conventional lasers and may prompt patients to stop therapy due to pain.…”
Section: Efficacy Of the 7% Lidocaine And 7% Tetracaine Peel For Dermsupporting
confidence: 80%
“…Jih and colleagues reported significantly greater pain relief with a 60-minute application of LT peel versus a placebo peel before 1,064-nm long-pulsed Nd:YAG laser treatment of leg veins. 15 The longer-wavelength lasers have been associated with a greater degree of pain than conventional lasers and may prompt patients to stop therapy due to pain. The randomized, double-blind, placebo-controlled trial demonstrated significantly lower median VAS scores at the LT peel sites than at the placebo application sites (22.0 mm vs. 44.5 mm; po.001).…”
Section: Laser Therapy For Leg Veinsmentioning
confidence: 99%
“…Similar results were found in another double-blinded, randomized, placebo-controlled study with laser treatment of leg veins. Significantly less pain was noted with lidocaine/tetracaine cream use compared to placebo by subjects and investigators ( P  < 0.001) [22]. …”
Section: Clinical Evaluation: Efficacymentioning
confidence: 99%
“…A summary of lidocaine/tetracaine cream studies for dermatologic laser procedures is presented in Table 1 [1, 2, 12, 22–26]. …”
Section: Clinical Evaluation: Efficacymentioning
confidence: 99%
“…An application time of 20 or 30 min was as effective as 60 min in achieving anesthesia, as measured by mean patient pain ratings using the visual analog scale. In another study, treatment with the LT peel for 60 min also led to patients experiencing significantly less pain vs. placebo for the PDL treatment of lower extremity telangiectases (0.5–1.5 mm in diameter) 8 . A third study showed that, after a 30‐min application of the LT peel to patients’ cheeks before nonablative laser treatment, the LT peel was found to provide safe and effective dermal anesthesia vs. placebo 9 …”
Section: Discussionmentioning
confidence: 99%